IMPLEMENTASI PEMBELAJARAN BERBASIS LOTS DAN HOTS PADA KELAS RENDAH DI SDN 49/IV KOTA JAMBI - Dwi Miza Rozalia (GURUKU, 2022)
This study aims to describe the implementation of LOTS and HOTS-based learning in the lower class at SDN 49/IV Jambi city. This research was conducted at SDN 49/IV Jambi City on 07 January to 07 February 2022. The research approach used was a qualitative approach with the type of case study research. The data in this study are in the form of a description of the implementation of LOTS and HOTS-based learning in low grades obtained through observations and interviews, which indicate that lower grade teachers have prepared LOTS and HOTS-based Learning Implementation Plans (RPP) with grade I, II, and III teachers. as the main data, interviews with lower grade teachers and school principals as well as documentation as supporting data. After collecting data, qualitative data analysis was then carried out. The results showed that the low grade teachers of SDN 49/IV Jambi City had implemented it in designing the LOTS and HOTS-based Learning Implementation Plans (RPP) with good categories. From the research results, the teacher has designed a Learning Implementation Plan (RPP) based on LOTS and HOTS. In LOTS and HOTS-based learning with categories C1, C2, C3 low-level thinking (LOTS) and categories C4, C5, and C6 high-order thinking (HOTS).